HOTS Based E-LKPD Assisted by Liveworksheets to Improve the Critical Thinking Skills of Fifth Grade Elementary School Students - Kadek Dwi Murtini; Desak Putu Parmiti; Kadek Yudiana (Universitas Pendidikan Ganesha, 2025)
The low level of students’ critical thinking skills in IPAS learning remains a significant issue, as indicated by their reliance on textbooks and limited ability to analyze problems and formulate alternative solutions. This condition highlights the need for the development of learning media that can promote higher order thinking skills. This study aims to develop and examine the feasibility, practicality, and effectiveness of Higher Order Thinking Skills (HOTS) based E-LKPD assisted by Liveworksheets in improving the critical thinking skills of fifth grade students. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects involved material experts, media experts, teachers, and fifth grade students. Data were collected through questionnaires and essay tests. Data analysis was conducted using qualitative and quantitative descriptive analysis, as well as statistical testing through a one group pretest posttest design. The results indicate that the HOTS based E-LKPD demonstrates very high validity with an average score above 4.80 and very good practicality based on teacher and student responses, with percentages exceeding 95%. The effectiveness test results show a significant improvement in students’ critical thinking skills after the implementation of the HOTS-based E-LKPD. Therefore, the HOTS-based E-LKPD assisted by Liveworksheets is considered feasible, practical, and effective for use in IPAS learning. This study implies the strengthening of HOTS-based digital learning media utilization and provides references for teachers in developing innovative learning media that support 21st-century thinking skills.